Harnessing markets for biodiversity : towards conservation and sustainable use - Biller, Dan; Organisation for Economic Co-operation and Development. Working Group on Economic Aspects of Biodiversity (Paris : OECD, 2003)
Biodiversity losses continue at an alarming rate. Policies are therefore urgently needed to promote the sustainable use and conservation of biodiversity. Governments and private sector actors are increasingly recognising the potential of harnessing markets to help arrest the degradation of biodiversity. The private provision of biodiversity products and services is proving to be quite feasible in some circumstances. Some biodiversity products and services are already being profitably marketed. Private markets also need to be supported by appropriate public policies. This publication provides a conceptual framework for market creation in the biodiversity policy arena, as well as several examples of where the use of markets can assist policy makers and society at large in the search for more sustainable use and conservation of biodiversity.
Prepared under the auspices of the OECD Working Group on Economic Aspects of Biodiversity; drafted by Dan Biller
Published in French as: Mobiliser les marches au service de la biodiversite: pour une politique de conservation et d'exploitation durable
Bibliography : p. 127-136
Also available electronically via World Wide Web in PDF format to subscribers of the following SourceOECD themes: Agriculture and food; Environment and sustainable development.
Keywords: Biological diversity -- Economic aspects; Biological diversity conservation -- Economic aspects; Wildlife products industry; Sustainable development